2021
DOI: 10.32674/jis.v11i3.2132
|View full text |Cite
|
Sign up to set email alerts
|

Walking on Gender Tightrope With Multiple Marginalities

Abstract: This phenomenological research explored how international female students understand the role of gender and national origin in their program experiences and how they cope with the challenges derived from their triple marginalities—gender, race/ethnicity, and foreign nationality. Based on in-depth interviews with 22 international female students enrolled in various STEM disciplines, we drew four thematic findings that illustrate the participants’ multiple marginalities and ironic coping strategies grounded in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 33 publications
0
18
1
Order By: Relevance
“…From another perspective, studies have focused on considering the socioeconomic and cultural profiles of female high school students who intend to pursue STEM careers (Kızılay et al, 2020). Meanwhile, recent research addresses the experiences of female graduate students in STEM careers regarding gender gaps and the challenges they face (Lim et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…From another perspective, studies have focused on considering the socioeconomic and cultural profiles of female high school students who intend to pursue STEM careers (Kızılay et al, 2020). Meanwhile, recent research addresses the experiences of female graduate students in STEM careers regarding gender gaps and the challenges they face (Lim et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Lin and Scherz (2014) found that Asian international graduate students were left out in summer when others went back to their home countries, and very few NNES students stayed on campus. Interestingly, a recent study has shown that Asian female international graduate students believe cultural aspects are unimportant because they believe academics are the more important aspect of graduate schooling (Lim et al, 2021). This belief leads students to spend extra time gaining academic knowledge rather than integrating cultural knowledge.…”
Section: Linguistic and Cultural Challengesmentioning
confidence: 99%
“…Female international graduate students can be considered a doubly marginalized group (Dutta, 2015) in the male-dominant engineering field. According to previous studies (Kuniyczka, 2019;Dutta, 2015;Lim et al, 2021), this group of students faces additional challenges, including marginalization and gender equality issues. In addition, female international students experience identity challenges, invisibility, insecurities, and stereotyping.…”
Section: Challenges For Female International Graduate Studentsmentioning
confidence: 99%
See 2 more Smart Citations